How can governments and investors successfully invoke positive human rights obligations in international investment law and arbitration? - Nicolò Andreotti (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2025)
Positive obligations stemming from international human rights law require states to realize fundamental rights. This Perspective argues that those human rights obligations may serve as basis for the conceptualization of a duty to regulate in investment law. Furthermore, it reflects on the implications this may have for investment arbitration.
Keywords: 330